ANALYSIS OF DIDACTICAL CONTRACTS ON TEACHING MATHEMATICS: A DESIGN EXPERIMENT ON A LESSON OF NEGATIVE INTEGERS OPERATIONS - Nyiayu Fahriza Fuadiah; Didi Suryadi; Turmudi Turmudi (Jurnal Infinity, 2017)
This paper presents the analysis of teaching of Math that took place in the classroom to identify the characteristics of didactical contracts that occur as part of a didactical situation. The design experiment was conducted on 31 seventh grade students and a mathematics teacher on negative integer operations lessons. The researchers analyzed the ongoing learning, how the didactical situation stages evolve in the teacher-student interaction that allows the formation of new knowledge or concepts in the student and how the teacher organizes the responsibility for achieving the learning objectives. The Analysis showed that students, at an early stage, can perform negative integers operations by utilizing the basic concepts they get in primary school. This concept can bridge into a new knowledge that identifies the properties of integer count operations and builds power of mind on problem-solving.Â